2002
DOI: 10.1148/radiographics.22.suppl_1.g02oc15s137
|View full text |Cite
|
Sign up to set email alerts
|

Viral Pneumonias in Adults: Radiologic and Pathologic Findings

Abstract: Numerous viruses, including influenza virus, measles virus, Hantavirus, adenovirus, herpesviruses, varicella-zoster virus, cytomegalovirus, and Epstein-Barr virus, can cause lower respiratory tract infection in adults. Viral pneumonia in adults can be classified into two clinical groups: so-called atypical pneumonia in otherwise healthy hosts and viral pneumonia in immunocompromised hosts. Influenza virus types A and B cause most cases of viral pneumonia in immunocompetent adults. Immunocompromised hosts are s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
202
1
22

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 310 publications
(244 citation statements)
references
References 44 publications
19
202
1
22
Order By: Relevance
“…Thin-section CT images of 11 patients with pneumonia revealed that 2 had diffuse bronchopneumonia, 1 had GGO, and the rest showed consolidation patterns. Although viral pneumonia is typically represented radiologically as poorly defined nodules and patchy areas of peribronchial GGO and air-space consolidation, other studies on adenovirus pneumonia in soldiers and children revealed lobar consolidation patterns, as seen in the present study (21,(28)(29)(30). However, we were able to detect more specific segments of lung infiltration than previous studies, indicating right lower lobe involvement (54.6z).…”
Section: Discussioncontrasting
confidence: 59%
“…Thin-section CT images of 11 patients with pneumonia revealed that 2 had diffuse bronchopneumonia, 1 had GGO, and the rest showed consolidation patterns. Although viral pneumonia is typically represented radiologically as poorly defined nodules and patchy areas of peribronchial GGO and air-space consolidation, other studies on adenovirus pneumonia in soldiers and children revealed lobar consolidation patterns, as seen in the present study (21,(28)(29)(30). However, we were able to detect more specific segments of lung infiltration than previous studies, indicating right lower lobe involvement (54.6z).…”
Section: Discussioncontrasting
confidence: 59%
“…• "Spectrum of Blunt Chest Injuries" [21]; and • "Viral Pneumonias in Adults: Radiologic and Pathologic Findings" [22].…”
Section: Reviewing Online Teaching Modules and Preselected Articlesmentioning
confidence: 99%
“…Dois pacientes apresentaram derrame pleural bilateral após D4, denotando piora do quadro congestivo. Com base no quadro radiológico, outros autores chamam atenção para um diagnóstico diferencial com outras causas de Pneumonia Atípica em pacientes imunocompetentes, como aquela pelos vírus Influenza tipos A e B. Quanto a pacientes imunocomprometidos, o quadro radiológico de SPCVH poderia ser confundido com pneumonias por fungos como o Pneumocistis carinii e o histoplasma, além daquelas de etiologia viral, por citomegalovírus, herpesvírus, vírus do sarampo e adenovírus 14 .…”
Section: Figuraunclassified
“…Os achados radiológicos pulmonares da SPCVH descritos como semelhantes aos encontrados em outras viroses, como influenzas, sarampo, adenoviroses, herpesviroses, varicella-zoster e citomegaloviroses 14 . No período inicial, apresenta opacidade peri-hilar e basal e acentuação lateral das fissuras.…”
unclassified